IMPLEMENTASI PERATURAN MENTERI DESA, PEMBANGUNAN DAERAH TERTINGGAL, DAN TRANSMIGRASI NOMOR 19 TAHUN 2017 TERKAIT PRIORITAS PENGGUNAAN DANA DESA TAHUN 2018 DI DESA BAKI PANDEYAN, KECAMATAN BAKI, KABUPATEN SUKOHARJO - Wiesesa, Herjuna Praba; Firdausy, Adriana Grahani (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This study analyzes the implementation of Ministerial Regulation of Village, Acceleration Development Backward Regions, and Transmigration Number 19 of 2017 Related The Priorities of the Village Funds Usage in bakipandeyan village, baki District, Sukoharjo Regency in 2018 and obstacles faced by village goverment. This legal research is an empirical and descriptive study with a qualitative approach. Sources of legal material in the form of primary and secondary legal materials. Legal material collection techniques are interviews with data reduction analysis techniques, data presentation and conclusions and verification. The results of the study show that the implementation of priority management of village fund use in Bakipandeyan village has been running well and in accordance with the provisions outlined in 5 stages, namely planning; distribution, realization, supervision and guidance, reporting and accountability of village funds. However, at the planning stage, the determination of the priority use of village funds is not fully appropriate because it only sets one priority, namely in the field of village development. Constraints faced include human resources in the village government apparatus that are less competent, delays in the distribution of village funds, differences in the expensiveness index of construction of districts and villages, the low work ethic of the community; village government agenda’s outside village development, and natural conditions.